2012
DOI: 10.1016/j.jgeb.2012.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular polymorphisms in Palestinian Figs (Ficus carica L.) as revealed by Random Amplified Polymorphic DNA (RAPD)

Abstract: The genetic diversity of 13 local Palestinian fig genotypes was investigated using RAPD markers. Among the 30 tested primers, 28 revealed various banding patterns and 2 generated no polymorphic bands. In addition, 13 primers (46.4%) produced good amplification products with high intensity and pattern stability. A total of 94 DNA fragments (loci), separated by electrophoresis on agarose gel were detected, ranging in size from 190 to 1300 bp. Of these fragments, 72 (76.6%) were polymorphic and 22 (23.4%) were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…[12], Papadopoulou et al [16] and Basheer-salimia et al [11] using RAPD markers or phenotypic markers [11]. In the current study, positive correlation was evidenced between morphological descriptors and RAPD markers.…”
supporting
confidence: 62%
See 3 more Smart Citations
“…[12], Papadopoulou et al [16] and Basheer-salimia et al [11] using RAPD markers or phenotypic markers [11]. In the current study, positive correlation was evidenced between morphological descriptors and RAPD markers.…”
supporting
confidence: 62%
“…The genetic similarity matrix showed an average similarity mean of 0.375. In an earlier RAPD study, Basheer-salimia et al [11] observed genetic diversity values ranging from 0.238 -0.477 with a mean of 0.358 among 9 different local Palestinian fig genotypes. The selected RAPD markers in this study revealed a wider range of genetic diversity than that observed by Basheer-salimia et al [11].…”
Section: Dendrogram Of Genetic Relationship (Similarity Matrix and CLmentioning
confidence: 94%
See 2 more Smart Citations
“…1 2 3 4 5 6 7 8 9 1 0 1 1 1 2 1 3 1 4 1 5 1 6 1 7 1 8 1 9 2 0 2 1 1 1.000 2 0.687 1.000 3 0.693 0.619 1.000 4 0.629 0.597 0.723 1.000 5 0.554 0.596 0.590 0.532 1.000 6 0.601 0.524 0.671 0.697 0.591 1.000 7 0.595 0.570 0.634 0.631 0.538 0.745 1.000 8 0.630 0.636 0.686 0.603 0.712 0.592 0.595 1.000 five times and 7.5 fold higher than RAPD, respectively (Dunham, 2011). RAPD molecular markers have been previously used for the genetic assessment of Palestinian fig genotypes and to determine the genetic variability in fig trees (Basheer-salimia et al, 2012;Rodrigues et al, 2012). Microsatellite markers were often preferred for characterizing different fig cultivars, including Egyptian, Spanish, and Tunisian figs, because they were codominant, hypervariable, and highly reproducible (Abou-Ellail et al, 2014;Achtak et al, 2009;Balas et al, 2014;Saddoud et al, 2005).…”
Section: Discussionmentioning
confidence: 99%